2015
DOI: 10.1073/pnas.1420850112
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of the Hippo pathway by adherens junctions and apical–basal cell polarity modules

Abstract: Adherens junctions (AJs) and cell polarity complexes are key players in the establishment and maintenance of apical-basal cell polarity. Loss of AJs or basolateral polarity components promotes tumor formation and metastasis. Recent studies in vertebrate models show that loss of AJs or loss of the basolateral component Scribble (Scrib) cause deregulation of the Hippo tumor suppressor pathway and hyperactivation of its downstream effectors Yes-associated protein (YAP) and Transcriptional coactivator with PDZ-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
120
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 47 publications
16
120
0
Order By: Relevance
“…While there are remarkable similarities between the Hippo pathways present in flies and mammals, there are also notable differences (Klezovitch and Vasioukhin 2015;Yang et al 2015). Hence, to determine whether DLG5 function in negative regulation of Hippo signaling is evolutionarily conserved, we used RNAi-mediated knockdown to analyze the signaling role of Dlg5 in flies.…”
Section: Dlg5 Inhibits Hippo Signaling During Fly Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…While there are remarkable similarities between the Hippo pathways present in flies and mammals, there are also notable differences (Klezovitch and Vasioukhin 2015;Yang et al 2015). Hence, to determine whether DLG5 function in negative regulation of Hippo signaling is evolutionarily conserved, we used RNAi-mediated knockdown to analyze the signaling role of Dlg5 in flies.…”
Section: Dlg5 Inhibits Hippo Signaling During Fly Developmentmentioning
confidence: 99%
“…To confirm whether expression of the dlg5 RNAi constructs resulted in misregulation of the Hippo pathway, we monitored Yki (Drosophila YAP/TAZ ortholog) activity using an established ex-LacZ reporter (Yang et al 2015). Expression of dlg5 RNAi using either engrailed or decapentaplegic drivers resulted in reduced LacZ staining (Fig.…”
Section: Dlg5 Inhibits Hippo Signaling During Fly Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Three apical-basal polarity complexes have been identified to date, including the CRB (Crumbs) complex (CRB/PATJ/PALS1), PAR complex (PAR3/PAR6/aPKC) and Scribble complex (SCRIB/DLG/LGL). These complexes work together to maintain apical-basal polarity.…”
mentioning
confidence: 99%
“…A variety of signals have been reported to either activate or inhibit the Hippo kinase cascade. In epithelial cells, apical-basal polarity regulates activities of the Hippo pathway through interactions between the upstream components and intercellular junction-associated proteins in response to cell-cell contact (40). Recent reports found that serum deprivation or energy stress also activates the Hippo pathway (41,42).…”
Section: Discussionmentioning
confidence: 99%